Learning Habits Shaping Mathematical Literacy: Lens Through the Chronology of Time and Cognitive Processes - Alghadari, Fiki; Yundayani, Audi; Genç, Murat (IndoMath: Indonesia Mathematics Education, 2022)
Mathematical literacy prepares future generations to deal with the challenges of a changing world. But, students' knowledge and abilities are still below the optimal level. This study aims to evaluate how students' learning habits, which are based on the chronology of time and cognitive processes, affect their mathematical literacy. This quantitative study employs an observational approach with vocational students in West Java who participated. This study examines the measurement and structural model up to the second-order levels. The findings revealed that the habit of reviewing had a substantial impact on factors in formulating mathematical models. However, the other components were not. Indications of how students adapt information lead to the condition that they do, but not in an ideal way at the logical-operational level. Therefore, learning is insufficient only during school hours due to cognitive capacity considerations, while the other is to build an independent learner attitude outside of school.